2020
DOI: 10.1007/jhep02(2020)084
|View full text |Cite
|
Sign up to set email alerts
|

Late-time-accelerated expansion arisen from gauge fields in an anisotropic background and a fruitful trick for Noether’s approach

Abstract: In this paper, a modified teleparallel gravity action containing a coupling between a scalar field potential and magnetism, in anisotropic and homogeneous backgrounds, is investigated through Noether symmetry approach. The focus of this work is to describe late-time-accelerated expansion. Since finding analytical solutions carrying all conserved currents emerged by Noether symmetry approach, is very difficult, hence regularly in the literature, the authors split the total symmetry into sub-symmetries and then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Tajahmad [75] has considered the similar relation to reconstructed the F(T) gravity. Most recent, Tajahmad [76] has shown that late time accelerated expansion arisen from gauge fields in an anisotropic background. It can be noted that for k becomes unity, the space-time reduces to be isotropic.…”
Section: Basic Formalism and Dynamical Parametersmentioning
confidence: 99%
“…Tajahmad [75] has considered the similar relation to reconstructed the F(T) gravity. Most recent, Tajahmad [76] has shown that late time accelerated expansion arisen from gauge fields in an anisotropic background. It can be noted that for k becomes unity, the space-time reduces to be isotropic.…”
Section: Basic Formalism and Dynamical Parametersmentioning
confidence: 99%
“…c η 1,a + b η 4,a = 0 , (6.183) introduces the constraint ã η 1,ã = 0, where ã now becomes the standard isotropic FLRW scale factor since a = b = c = ã. This extra constraint does not appear in the standard f (T ) FLRW Noether equations.Next, TEGR in the presence of a scalar-electromagnetic field coupling is considered[1005] …”
mentioning
confidence: 99%
“…Cosmological models are investigated via several powerful tools: exact solutions, phase space [25,26], B-function method [27], Noether symmetry approach [28][29][30][31], Beyond Noether symmetry approach (B.N.S.) [32], Noether symmetry approach using CSSS-trick [33], Reconstruction methods [34][35][36][37][38], etc. Recently, a new strategy to the reconstruction of f (R)-gravity models using Raychaudhuri equation has been proposed by Choudhury et al [1].…”
Section: Introductionmentioning
confidence: 99%